LA DECONSTRUCTION DE L’EUROCENTRISME PHILOSOPHIQUE PAR LES PHILOSOPHES AFRICAINS - Bauvarie MOUNGA (Studia Universitatis Babeș-Bolyai. Philosophia, 2023)
Deconstruction of the Philosophical Eurocentrism by African Philosophers. Eurocentrism is a current that is manifested by the refusal, disdain and depreciation of all knowledge abroad in favor of European cultures. So it is question of the promotion of Western Europe as the very center of the political, economic and philosophical thinking. Precisely, given the philosophical eurocentrism, African thinkers are trying to reach more visibility and to question this state of affairs. The purpose of this paper is to describe and analyze the different ways in which African philosophers criticize eurocentrism and to study the different philosophical currents set up to provide more visibility to African philosophy. The paper has two sections: philosophy and the cult of eurocentrism and the various means of affirmation of African philosophy.